High-Throughput Robotic Synthesis and Photoluminescence Characterization of Aqueous Multinary Copper–Silver Indium Chalcogenide Quantum Dots - Stroyuk, Oleksandr; Raievska, Oleksandra; Langner, Stefan; Kupfer, Christian; Barabash, Anastasia; Solonenko, Dmytro; Azhniuk, Yuriy; Hauch, Jens; Osvet, Andres; Batentschuk, Miroslaw; Zahn, Dietrich R. T.; Brabec, Christoph (Particle & Particle Systems Characterization, 2021)
The feasibility of a high-throughput robot-assisted synthesis of complex Cu1-xAgxInSySe1-x (CAISSe) quantum dots (QDs) by spontaneous alloying of aqueous glutathione-capped Ag–In–S, Cu–In–S, Ag–In–Se, and Cu–In–Se QDs is demonstrated. Both colloidal and thin-film core CAISSe and core/shell CAISSe/ZnS QDs are produced and studied by high-throughput semiautomated photoluminescence (PL) spectroscopy. The silver-copper-mixed QDs reveal clear evidence of a band bowing effect in the PL spectra and higher average PL lifetimes compared to the counterparts containing silver or copper only. The photophysical analysis of CAISSe and CAISSe/ZnS QDs indicates a composition-dependent character of the nonradiative recombination in QDs. The rate of this process is found to be lower for mixed copper-silver-based QDs compared to Cu- or Ag-only QDs. The combination of the band bowing effect and the suppressed nonradiative recombination of CAISSe QDs is beneficial for their applications in photovoltaics and photochemistry. The synergy of high-throughput robotic synthesis and a high-throughput characterization in this study is expected to grow into a self-learning synthetic platform for the production of metal chalcogenide QDs for light-harvesting, light-sensing, and light-emitting applications.
CRIS-Team Scopus Importer:2021-09-10
Keywords: combinatorial synthesis; semiconductor nanocrystals; spontaneous alloying; ternary chalcogenides; time-resolved photoluminescence